Physeal injuries in children`s and youth sports: reasons for concern? - Caine, D.; DiFiori, J.; Maffulli, N. (British Journal of Sports Medicine, 2006)
A systematic review of the literature on the frequency and characteristics of sports related growth plate injuries affecting children and youth in organised sport was carried out. Both acute and chronic physeal injuries related to participation in sports have been reported to occur, although injury incidence data are somewhat limited. Of particular concern is the growing number of stress related physeal injuries, including those affecting the lower extremities. Although most physeal injuries appeared to resolve with treatment and rest, there is also evidence of growth disturbance and deformity. Possible injury risk factors and countermeasures are discussed, and suggestions for directing future research provided.